The Three Battles of el Alamein Rare Photographs from Wartime Archives - Diamond, Jon (Images of War Series, 2023)
Chapter One -- Desert Combat in Egypt and Cyrenaica 1940-1942 -- Map 1. The Mediterranean Theatre of Operations, 1940-1943. -- Chapter Two -- Terrain and Weapons -- Chapter Three -- Commanders and Combatants -- Chapter Four -- The First Battle of El Alamein -- Map 2. The First Battle of El Alamein, 1-27 July 1942. -- Chapter Five -- The Battle of Alam el Halfa -- Map 3. The Battle of Alam el Halfa, 30 August-5 September 1942. -- Chapter Six -- The Second (Main) Battle of El Alamein -- Map 4: The Second (Main) Battle of El Alamein, 23 October-4 November 1942. -- Epilogue -- Bibliography -- Back Cover.